Boronic ester-based dynamic covalent ionic liquid gels for self-healable, recyclable and malleable optical devices. Issue 46 (16th November 2018) - Tang, Jiaqi; Yang, Jinglun; Yang, Hui; Miao, Rong; Wen, Ruijuan; Liu, Kaiqiang; Peng, Junxia; Fang, Yu
Abstract : Excellent light transmittance and non-volatility of the dynamic ionic liquid gels make them become ideal soft optical materials. Abstract : Dynamic covalent ionic liquid (IL) gels have been proved to be promising materials for soft optical devices which possess the advantages of other dynamic gels but avoid shrinking. The focal length of the planoconvex lens made from the gels is tunable and the prism from them shows an excellent beam splitting property. Damaged devices could be re-covered via self-healing or re-molding.